Artificial Intelligence (AI) as a tool for predicting the financial culture of a country - Borreguero Arias, David; Gómez Martínez, Raúl; Alard Josemaría, Julio; Prado Román, Camilo (Journal of Management and Business Education, 2024)
Artificial Intelligence (AI) currently presents different applications that allow, through data processing, the possibility of learning, predicting and adopting solutions in different fields of knowledge including the financial field. This research essay aims to analyze the capacity of Artificial Intelligence (AI) and supervised learning to predict the level of financial culture that individuals possess. For this purpose, 11 predictors previously selected for their possible influence on financial culture, are proposed and compared with the target variable (level of financial culture). The results obtained show that each of the 11 individual-level predictors correlate with the level of financial culture that each individual claim to have. In this respect, a general high or very high perception of the target variable is shown. However, considering the accuracy of the reference, the research shows that as the number of predictors is smaller, the accuracy of the reference decreases.